A facile frequency tuning strategy to realize vibration‐based hybridized piezoelectric‐triboelectric nanogenerators. Issue 1 (30th August 2022) - Liu, Long; Shi, Qiongfeng; Guo, Xinge; Zhang, Zixuan; Lee, Chengkuo
Abstract: With increasing requirements of the Internet of things (IoT) functioning with wireless sensor networks (WSN), a self‐sustainable power supply has become an important pursuit in long‐term working. The cantilever‐based energy harvester is one of the most widely used devices for converting vibrations into electrical energy, while still challenged by restricted frequency bands toward practical applications. Here, a novel, feasible and cost‐effective strategy for tuning the cantilever's resonant frequency is proposed. By applying 3D printed thin sheets as extensions, the original single vibration mode is promoted into two relatively independent vibration modes tuned with extensions' type, length, thickness, and proof masses. Hybridized piezoelectric‐triboelectric nanogenerators are introduced to improve capacitor charging ability and potential vibration detection. Furthermore, a four‐cantilever coupling design with different tuning parameters is investigated and enables wireless demonstrations of monitoring environmental temperature/humidity and carbon dioxide concentration, which is prospective as self‐sustainable protection for workers in tunnels or underground constructions. Abstract : The cantilever's single vibration mode is found to turn into two relatively independent vibration modes as the 3D printed sheets are applied as extensions. Thus, a four‐cantilever coupling design based on hybridized piezoelectric‐triboelectric nanogenerators is developed with different extensions. Finally, demonstrations of wirelessly monitoring environmental temperature/humidity and carbon dioxide concentration are realized in self‐sustainable ways.